THE EFFECT OF BIG FIVE PERSONALITY AND ORGANIZATIONAL COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN PT. ARKONINE - Purwana, Dedi; Marsofiyati; Widyanti, Jovita (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine the effect of big five personality and organizational commitment on organizational citizenship behavior in PT Arkonin employees. The research was conducted at PT Arkonin for 4 months from April to August 2021. The method used in this study was a quantitative method, collecting data using a questionnaire conducted on 124 employees of PT Arkonin. The data analysis technique used is multiple regression analysis which is processed with the SmartPLS 3.0 program. The first research hypothesis is the influence of big five personality on organizational citizenship behavior has a positive and significant effect with the results of t-statistics showing 6.444 > 1.96 and p-values 0.000 < 0.005 then H0 is rejected and Ha is accepted, the second hypothesis is the effect of organizational commitment on organizational citizenship behavior has a positive and significant effect with t-statistic results showing 3.818 > 1.96 and p- values 0.000 < 0.005 then H0 is rejected and Ha is accepted, and the third hypothesis is the influence of big five personality organizational commitment on organizational citizenship behavior with the F test, namely F count > F table that is 78.901 > 3.920 then H0 is rejected and Ha is accepted.